Historische formelhafte Wendungen als Konstruktionen: Möglichkeiten und Grenzen der diachronen Konstruktionsgrammatik - Filatkina, Natalia (Linguistik Online, 2018)
Construction Grammar and research on phraseology have both commenced as purely synchronically oriented subfields of linguistics and are nowadays only starting to gain a historical dimension. Both disciplines put such units of language in the center of their research that I address in the present paper as formulaic patterns. The paper aims to discuss the possibilities and limits of multifold interactions between the two subfields of linguistics with regard to historical formulaic language. An overview of the state of the art in the field of diachronic Construction Grammar (Section 2) is followed by reflections on historical phraseology that can already partially offer some answers to the questions posed by the Construction grammar only now (cf. Section 3). The case studies (Section 4) provide an empirical basis for the preceding theoretical considerations and are based on the data of the Research Group HiFoS at the University of Trier. The data consist of about 32.000 fully annotated formulaic patterns from historical German texts since the beginning of the written tradition in the 8th century to 1650.